Otimização do processo de extração de compostos bioativos do zingiber officinale (gengibre) para incorporação em lipossomas e estudo do potencial em aplicações farmacêuticas - Nardino, Danielli Andrea (2021)
Ginger (Zingiber officinale Roscoe) is a plant that has gained prominence by the scientific community for presenting several pharmacological properties resulting from the presence of bioactive compounds, such as antibiotic, anti-inflammatory, antimicrobial, antioxidant and also antitumor action. Despite the potential of bioactive compounds, these in turn are susceptible to external agents, thus, encapsulation appears as an alternative to protect these compounds against environmental stress and chemical degradation, in addition to increasing stability and bioavailability for a certain period. . Among the nanocarrier systems, liposomes have greater relevance due to their structure, consisting of phospholipids that have a polar and a nonpolar region, which, when in an aqueous medium, self-organize forming vesicles that enable the encapsulation of hydrophobic compounds and, mainly, they do not present toxicity to the organism. In view of the pharmacological potential of ginger extract, this work aimed to optimize the extraction of bioactive compounds and the evaluation of the extraction through the DPPH, ABTS and iron (II) chelating ability tests, with the best extract (prepared at 60°C for 12 h) the kinetic parameters for the DPPH and ABTS reactions were determined, in which the reaction orders were 4 and 5, respectively, with the activation energy varying between 38.6 and 43.0 kJ mol-1. The characterization of the best extract was performed using TGA/DTA, DSC and mass spectrometry tests, the evaluation of the biological potential by the antitumor action and inhibition of the enzyme acetylchoinesterase (AChE) and the production of liposomes made with soy lecithin by the method of ethanol injection, with different proportions of the extract. The physicochemical evaluation of liposomes was based on hydrodynamic diameter, zeta potential and encapsulation efficiency. By thermal analysis, it was observed that ginger has low resistance, with degradation from approximately 40 °C. Regarding the tests with the AChE enzyme, the extract did not show a response in terms of inhibitory action, however, it was shown to be non-toxic, a characteristic that allows application for treatment in cells. It showed an antitumor effect from the administration of 200 μg mL-1 of free extract. The results of the particle size analysis showed that the liposomes produced have low polydispersity values, with a hydrodynamic diameter ranging from 139.50 to 168.15 nm from 10 to 30% of the encapsulated extract, respectively, and the zeta potential varied from -29.9 to -36.0 mV, these results enable the pharmaceutical and/or food application of liposomes. By the encapsulation efficiency test, no significant difference was observed between liposomes produced with 20 and 30% of ginger extract.